2022
DOI: 10.1002/rra.3947
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring invasive alien macroinvertebrate species with environmental DNA

Abstract: Regular monitoring of ecosystems can be used for the early detection of invasive alien species (IAS), and provide information for management and preventing them from becoming established or advancing into new areas. Current methods of monitoring freshwater systems for IAS can be both financially costly and time‐consuming, with routine monitoring often carried out at low intensity and at only a small number of sites. In this study, we evaluate how environmental DNA (eDNA) metabarcoding for monitoring freshwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Additional next-generation sequencing technologies, such as environmental DNA (eDNA), have been proven successful in detecting C. sowerbii (e.g. Blackman et al, 2022). Such detections can be produced even when no medusa sightings exist and are potentially beyond the medusa developing period as the polyp stage is present year-round.…”
Section: Phylogenetic Relationships Of Canadian and American Specimensmentioning
confidence: 99%
“…Additional next-generation sequencing technologies, such as environmental DNA (eDNA), have been proven successful in detecting C. sowerbii (e.g. Blackman et al, 2022). Such detections can be produced even when no medusa sightings exist and are potentially beyond the medusa developing period as the polyp stage is present year-round.…”
Section: Phylogenetic Relationships Of Canadian and American Specimensmentioning
confidence: 99%
“…Second, the range of methodological techniques showcased by the papers highlights that tackling the challenges of biological invasions requires a combination of methods ranging from controlled experiments which may provide explicit evidence for small scale processes (e.g., Coughlan et al, 2022; Sanders & Mills, 2022), through to modelling approaches to gain a broadscale view of invasion dynamics (Larson et al, 2022; Maimela et al, 2022). Field studies which aim to investigate site specific / regional patterns provide in‐situ validation of theories and enable incorporation of potentially interacting and confounding factors to be considered (e.g., Blackman et al, 2022; Bolpagni & Dalla Vecchia, 2022; Mathers et al, 2022; Salgado et al, 2022). Third, a common theme within many papers is the role of anthropogenic modifications in promoting the spread and ecological implications of biological invasions (e.g., Santas et al, 2022; Makherana et al, 2022), with habitat heterogeneity potentially conferring some form of invasibility resistance (e.g., Salgado et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%
“…One method which is increasing in application in the field of invasion biology is the use of environmental DNA (eDNA; Larson et al, 2020). Blackman, Brantschen, Walser, Wüthrich, and Altermatt (2022) compare the effectiveness of traditional kick-sampling with eDNA sampling in detecting invasive macroinvertebrate species at both a national and catchment scale level in Switzerland. Their results suggest that kick sampling is more efficient at detecting several well-known target species but that complimentary eDNA samples may detect some INNS that are otherwise overlooked.…”
Section: Monitoring and Managing The Spread Of Innsmentioning
confidence: 99%
“…However, many microscopic taxa living in the plankton can be invasive as well, like Oithona davisae (Yildiz et al, 2016) and other planktonic calanoid copepods (Beaver et al, 2019) or other zooplanktonic species (Kelly et al, 2013). Many of those invaders are overlooked for the intrinsic difficulty of sampling and the need of specialized laborious expertise for their identification (Feckler et al, 2014;Blackman et al, 2022). Environmental DNA (eDNA) and metabarcoding can help in this, since obtaining individuals for further taxonomic analysis is not necessary (Uchii et al, 2016;Borrell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The organisms present in the environment are then identified through high-throughput sequencing a phylogenetically informative DNA region. Many studies have demonstrated that metabarcoding on DNA samples reflect the existing biodiversity in aquatic environments (e.g., Fernandez et al, 2021;Blackman et al, 2022). The technique is useful for the identification of exotic plankton species; for example, eDNA extracted from water samples in French Polynesia allowed researchers to identify planktonic NIS that suggest changes in the trophic chain from its lower links .…”
Section: Introductionmentioning
confidence: 99%